Rethinking public organizations as knowledge-oriented and technology-driven organizations - Mauro Romanelli (Management dynamics in the knowledge economy, 2017)
Public organizations should rediscover the role of knowledge as a source for designing and implementing internal processes and adopt a knowledge management approach by using and managing technology as means and enabler for building a citizen-centered public management, sustaining democratic and civic values by promoting openness and fostering participation in order to encourage collaboration with citizens for co-producing public services and co-creating public value. Information and communication technologies are driving public organizations as responsive institutions in front of the citizens to proceed towards sustainability as a principle of governance for promoting the public interest and sustaining active citizenship, enhancing both collaboration and interaction between citizens and public administration. Introducing and actively implementing technology in government helps rethink public organizations as knowledge oriented and information based organizations seeking sustainability by involving citizens, businesses and other stakeholders for public value creation, enabling access to information, sustaining openness, transparency and accountability in order to engage citizens and encourage them to be included and actively participate in democratic public life, involving citizens to assume the responsibility for co-production of public services and fostering citizen participation in public policy choices. Technology opens up new opportunities for public organizations seeking sustainability by rediscovering knowledge as source and strategic asset following a knowledge management approach for designing and implementing democratic and administrative processes, redesigning the relationship with citizens, building public trust, encouraging citizen participation and sustaining co-production of public services.
10.25019/MDKE/5.4.06; 10.25019/MDKE/5.4.06; 2819566-8; 2392-8042; Management dynamics in the knowledge economy; 823675920